THE ROLE OF ISLAMIC EDUCATION IN SHAPING THE CHARACTER OF GENERATION Z IN THE SOCIAL MEDIA ERA - Nur Syawarnih; Umiarso (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study discusses the role of Islamic education in shaping the character of Generation Z in the social media era. Generation Z has grown amid the rapid development of digital technology and social media, resulting in characteristics closely related to internet use, digital communication, and fast access to information. On the other hand, the growth of social media has also created several negative impacts, including moral decline, weak communication ethics, consumerist behavior, individualism, and low self-control among young people. This study employs a library research method by reviewing journals and literature related to Islamic education, Generation Z character development, and social media. The findings show that Islamic education has a strategic role in shaping Generation Z character through the internalization of moral values, strengthening spirituality, digital literacy, and learning that adapts to technological development. In addition, social media can be used as a more interactive, attractive, and relevant medium for Islamic Religious Education learning in accordance with the characteristics of Generation Z. Therefore, Islamic education needs to innovate technology-based learning in order to form a generation that is not only excellent in science and technology, but also possesses character, morals, and ethics in accordance with Islamic values.